Endorser credibility and its influence on the attitude toward social media advertisement in Malaysia - Samat, Muhammad Faizal; Hashim, Haslinda; Raja Yusof, Raja Nerina (Society of Interdisciplinary Business Research, 2015)
The evolution of technology has made many companies shift their advertising strategy to a different medium. Nowadays rather than solely focusing on traditional advertising platforms, marketers have moved towards communicating messages about their products and services using online advertising platforms such as online websites. One particularly popular online advertising platform being utilized by marketers is social media. There are many studies about the effectiveness of using celebrity endorser in advertisements and the results shows a positive relationship but it seems that there are limited researches in social media as a medium. Since the increasing advertising budget was spend in internet, it had shown the internet advertising become prominent in Malaysia. With regard to the significance of the internet advertising to influence the consumer, this paper aims to assessed the impact of endorser credibility on attitude in social media advertisement. The study carried out in Malaysia using 200 respondents. Three elements to measure the endorser credibility, that are, attractiveness, expertise and trustworthiness. To examine the relationship, this paper employs a SPSS test that is capable of testing the relationship between the variables. The analysis confirmed that, attractiveness, expertise and trustworthiness is significance with attitude toward social media advertisement. Overall, the study provides supportive evidence on the impact of using endorser in social media advertisement and the results help businesses to formulate better strategy in advertising.